Lateral soil pile structure interaction assessment for semi active tuned mass damper buildings. (February 2021) - Ghorbanzadeh, Mohammad; Uygar, Eris; Sensoy, Serhan
Abstract: Using Lateral load-displacement curves (p-y curves) which is recommended by American Petroleum Institute (API) guideline, is typically used as a design approach for analysis of soil-pile-structure interaction due to its simplicity. The soil-pile structure interface has two separate parts of interaction; kinematic and inertial interaction. Both types of interaction must be measured accurately for the structures with dampers to determine the optimum parameters for design. For structures equipped with semi active tuned mass damper (STMD) on deep foundation, determination of the optimum STMD characterizations are completely related to the dynamic attitude of the structure. Hence, in this study, first the accuracy of general p-y equation for buildings with STMD which have short period on deep foundations are evaluated. Then, three dimensional continuum method (finite element method) is used and the general equation of API are updated to provide compatibility. The results showed that the accuracy of spring method (p-y curves method) is very poor in estimation of dynamic response of the structure. A modified API equation is proposed to improve the accuracy and reduce the degree of error for the data set provided. However, it is concluded that the three dimensional continuum method is still a more trustworthy approach for the type of problem investigated in this paper.